Advantages Of Laparoscopic Hernioplasty in Obesity Women of Fertile Age (Eurasian Medical Research Periodical, 2024)
In the traditional treatment of external abdominal hernias in women of fertile age in the early postoperative period, the frequency of surgical complications was 13.4%; in the long-term period, 8.5% of patients had a recurrence of the hernia. A critical analysis revealed that the unsatisfactory results were due to the shortcomings of tactical approaches in the ability to perform alloplasty in women of reproductive age